Tłumaczenie jako jedna z technik językowych działań mediacyjnych. Wyniki badania wstępnego - Kucharczyk, Radosław (Neofilolog, 2024)
The aim of this article is to reflect on the place of translation – understood as one of the forms of mediation activities – in the process of language education. The theoretical content is preceded by a description of the author’s own study conducted among Polish-speaking students learning French in bilingual classes. The aim of the analysis is to show the elements of translation that fit into the assumptions of text mediation which should be paid attention to in the process of language learning and teaching, and how to examine texts mediated by students.